Mid-continent methane emissions study - Zimmerle, Daniel; Howell, Cynthia; Nummedal, Dag; Smits, Kathleen (Colorado State University. Libraries, 2016)
In this first-of-its-kind Mid-Continent Methane Emissions Study, researchers from across the region, universities, government agencies, and industries joined forces determined to reconcile discrepancies between measurement methods in methane loss rates from onshore oil and gas developments in multiple basins. Seeking to bring public and private sectors better understanding of this issue, the combined resources of these groups resulted in weeks of field study and conclusive data. This team discovered that in other studies, top-down measurements reported much higher methane leak rates than bottom-up methods. Equipped with that knowledge this team used paired measurements from the same natural gas sources to determine the inconsistencies in measurement methods. The result of a field campaign, which happened over a five week period from late September to early October, 2015 is described in the study overview.
RPSEA project
Energy Institute
Keywords: methane emissions